2018
DOI: 10.3390/toxins10030103
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Dietary Exposure to Low Levels of Domoic Acid and Problems with Everyday Memory: Research to Public Health Outreach

Abstract: Domoic Acid (DA) is a marine-based neurotoxin. Dietary exposure to high levels of DA via shellfish consumption has been associated with Amnesic Shellfish Poisoning, with milder memory decrements found in Native Americans (NAs) with repetitive, lower level exposures. Despite its importance for protective action, the clinical relevance of these milder memory problems remains unknown. The purpose of this study was to determine whether repeated, lower-level exposures to DA impact everyday memory (EM), i.e., the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Most patients improve within 24 h to 12 weeks, but when consumers develop serious neurological damage, they can die [ 45 ]. Autopsies of deceased individuals have shown brain damage characterized by neuronal necrosis and astrocytosis particularly in the hippocampus, a cerebral region associated with memory and learning, which leads to the diagnostic label: amnesic shellfish poisoning (ASP) [ 44 , 46 , 47 ]. Anterograde memory disorder was described as a prominent feature and was considered a hallmark of DA intoxication [ 48 ].…”
Section: Domoic Acidmentioning
confidence: 99%
“…Most patients improve within 24 h to 12 weeks, but when consumers develop serious neurological damage, they can die [ 45 ]. Autopsies of deceased individuals have shown brain damage characterized by neuronal necrosis and astrocytosis particularly in the hippocampus, a cerebral region associated with memory and learning, which leads to the diagnostic label: amnesic shellfish poisoning (ASP) [ 44 , 46 , 47 ]. Anterograde memory disorder was described as a prominent feature and was considered a hallmark of DA intoxication [ 48 ].…”
Section: Domoic Acidmentioning
confidence: 99%
“…In humans, a high, single-exposure dose of DA can cause amnesic shellfish poisoning (ASP), which involves symptoms of amnesia, seizures, coma, and in extreme cases, death. Even chronic, low-level consumption of DA may lead to kidney damage, cognitive deficit, and impairment of fetal development, making DA outbreaks an important human health problem (710). Similar neurotoxic symptoms have been observed in birds and marine mammals such as sea lions, which suffer spatial memory impairment linked to DA consumption, likely leading to increases in sea lion strandings (11).…”
mentioning
confidence: 99%
“…Recent results from an environmental epidemiology study focused on chronic, low dose DA exposure reported that the high consumption of razor clams (>15 per week) in adult members of three Native American tribes living on the Western coast of the U.S. was associated with significant memory decrements when compared to a reference group of non-consumers or low-consumers (Grattan et al, 2016b). Deficits in memory were significant enough to impact daily living skills (Grattan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%